SERVICIILE DE REFERINŢĂ PRESTATE DE BM „B.P. HASDEU” COMUNITĂŢII CHIȘINĂUIENE, ÎN EPOCA INFORMAŢIONALĂ - TRICOLICI, bibliotecar principal, CID „Chișinău”, Claudia (BIBLIOPOLIS, 2020)
The article is about the reference servicies offered by the Municipal Library B.P. Hasdeu, its evolution in time, from the reference librarian’s function in the past to the present; and the changes produced in the bibliographical and informational activities.